The Application of Fragmentation Techniques on Distributed Database: An Overview - Sharifah Hafizah, Sy Ahmad Ubaidillah; Noraziah, Ahmad; Mohd Helmy, Abdul Wahab; Ainul Azila, Che Fauzi; Roslina, Mohd Sidek (2017)
Distributed processing is an effective way to improve performance of database systems. Hence, fragmentation and proper allocation of fragments across various sites of the network is considered as a key research area in distributed database environment. Data can be stored in different computers by fragmenting the whole database into several pieces called fragments. Each piece is stored at a different site. Fragmentation techniques had been proved by many research in improving the performance of the database system, reduce the transfer cost and access time. This paper presents an overview of various fragmentation techniques on distributed database.